Respon Jagung Sayur (Baby corn) Terhadap Ketersediaan Air dan Pemberian Bahan Organik - Kaswan Badami (Universitas Trunojoyo Madura, 2008)
This study aimed to find out the response of baby corn to the soil water availability and organic matter application The research was carried out at the horticultural garden of Socah and conducted from May to July 2007. Completely randomized block design with two factors and three replications was applied in this study. The first factor was the application of organic matter, consisting of two levels, namely M1 (without organic matter addition), M2 (the mixture of red Mediterranean soil and organic matter 2:1). The second factor was the capacity of water availability consisted four levels, namely: A1 (100% field water capacity), A2 (83% of field water capacity), A3 (66% field water capacity), and A4 (50% field water capacity). The results showed that the treatments had interaction with plant height, leaf area, and cob length. It also had a significant influence (p equal 0.001) on leaf number, cob diameter dan wet cob weight. The combined M2A1 showed the best result concerning with plant height, leaf area, and cob length at the harvest time. The application of organic matter (M2) could increase wet cob weight and cob diameter. Water availability on 100% field capacity (A1) could increase wet cob weight and cob number.